MUDIG transforms global vocational education by enhancing engagement: MUDIG mentransformasi pendidikan kejuruan global dengan meningkatkan keterlibatan - Olvyya, Amaydhi; Hasanah, Fitria Nur (Universitas Muhammadiyah Sidoarjo, 2024)
This research introduces MUDIG (Mobile Understanding Digital Graphic) learning media, designed to enhance class X students' comprehension of Graphic Design at Diponegoro Vocational School, Sidoarjo. Utilizing the Research and Development (R&D) methodology with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, the study aimed to address the lack of engaging learning materials in vocational education. Results from a small-scale trial showed positive student responses, with an average assessment of 86.6%, alongside high suitability ratings from expert validation. Student feedback emphasized increased interest, motivation, and understanding of the subject matter. These findings underscore the potential of innovative media like MUDIG to improve teaching and learning outcomes in vocational education, suggesting avenues for further exploration and implementation in broader classroom contexts. Highlight: MUDIG enhances Graphic Design learning in vocational education. Students respond positively, showing increased interest and comprehension. R&D methodology, ADDIE model ensure structured development and evaluation. Keyword: MUDIG, Graphic Design, Vocational Education, R&D Methodology, ADDIE Model